In the Federal Court of Australia, Western Australia District Registry, General Division (no. WAD 6006 of 2003) between Anthony Bennell, Alan Blurton, Alan Bolton and ORS (SNC) (applicant) and State of Western Australia & others (respondents) : applicant's historical report - Host, John T. (John Thomas), 1946-; South West Aboriginal Land & Sea Council Aboriginal Corporation (Victoria Park, W.A. : South West Aboriginal Land & Sea Council, 2005)
Report tracing the history of the Noongar people in the South-West of Western Australia since European settlement; prepared on behalf of the South West Aboriginal Land & Sea Council for the single Noongar native title claim in the Federal Court in Perth.
Cover title.
Bibliography: leaves 278-288.
Keywords: Noongar (Australian people) -- History; Aboriginal Australians -- Western Australia -- South-West -- History; Aboriginal Australians -- Land tenure -- Western Australia; Native title (Australia) -- Western Australia -- South-West.; Native title - Claims; Race relations - Violent; Noongar / Nyungar / Nyungah people (W41) (WA SI50); Colonisation; Western Australia -- History